Konstruktion oder Evolution der Zeit? - Mathias Gutmann (Rechtsgeschichte : Rg : Zeitschrift des Max-Planck-Instituts für Europäische Rechtsgeschichte, 2007)
As there are no time-independent biological processes, time seems to be a biological phenomenon kat echen. This statement is true not only for developmental or evolutionary transformations, which show specific temporal and spatial patterns, but for all known physiological, genetic or molecular-biological as well as ecological or populational processes. The remarkable time dependency of all life-processes attracted the attention of biologists and philosophers – Whitehead’s concept of actual entities which constitute the monad-like centrepoints of his Leibnizian universe provide a perfect example. Despite the relevance of temporal descriptions, their methodological status in the sciences is often unclear.The aim of this paper is to present at least some of the most important non-empirical aspects of any scientific treatment of temporal phenomena. Following a constructivist approach, the introduction of temporal language particles is traced back to explicit contexts of human everyday life practices and action. »Time« is considered to represent a specific façon de parler, which allows us to deal with temporal aspects of processes and world-states, which themselves are the very subject-matter of scientific descriptions. Following this line of argument, the attempt to derive time as an epistemological precondition of subjective knowledge on grounds of biological descriptions in the perspective of an »evolutionary concept of knowledge« (Evolutionäre Erkenntnistheorie) is rejected by proving the pre-empirical, categorical status of temporal concepts. Accordingly, an evolutionary derivation of time is shown to be impossible: in contrast to naturalistic approaches, time is either to be understood as a condition of the possibility of knowledge itself (i. e. of scientific knowledge a fortiori) or it designates temporal aspects of natural processes, which are described in reference to the presupposed categories of knowledge. In both cases, »time« is neither a »natural« nor a biological object.